2021
DOI: 10.1007/s40120-021-00287-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Attentional Bias in Fibromyalgia: A Pilot ERP Study of the Dot-Probe Task

Abstract: Introduction:The present research investigates the neural correlates of attentional bias in fibromyalgia (FM) with a dot-probe task performed during an electroencephalogram (EEG) recording. Methods: For this purpose, 30 female participants were recruited, divided into two groups: a group of patients with FM (FM, n = 15, M age = 51.87) and a healthy control group (HC) (HC, n = 15, M age = 46.13). Results: The results did not show behavioral differences between groups, but the EEG results showed that healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Other studies seem to support the thesis of generalized attentional deficits in FM and augmented emotional processing of the target stimuli [ 28 30 ].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies seem to support the thesis of generalized attentional deficits in FM and augmented emotional processing of the target stimuli [ 28 30 ].…”
Section: Introductionmentioning
confidence: 89%
“…The visual analogue scale was used to evaluate pain intensity, sleep quality and fatigue. This interview was used in another previously published study [ 28 ]. The interview guide is in the supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…Alicart et al (2020) identified that gossip information was more deeply remembered than trivia, and the related P300 amplitude was larger, indicating that it was positively related to the attention state [49]. Cardoso et al (2021) tried to distinguish the cognitive processes expressed by P300 and LPP, in which the former was associated with concentration, whereas the latter was more closely related to emotional changes [50]. Liu et al (2022) used P300 to explore the impact of social norms on the willingness to use recycled water.…”
Section: Event-related Potentials Related To the Cognitive Processmentioning
confidence: 99%